Emerging Roles of Small and Medium Enterprises in the Fourth Industrial Revolution in Africa - Adegbite, Waliu M.; Govender, Cookie M. (Mediterranean Journal of Social Sciences, 2021)
The Fourth Industrial Revolution (4IR) is more than just technology-driven change, disruptive innovation impacts core industries, including the informal sector. Expectedly, the revolution will raise the level of innovation and creativity of the manufacturing SMEs through the Industrial Internet of Things (IIoT). Unfortunately, fewer studies attempted to examine the knowledge level of SME’s adoption of 4IR technologies, and their benefits to the sector in low-income countries, especially in Africa. This research paper takes a closer look at the expected roles of SMEs. It examines the emerging roles of SMEs in the 4IR towards sectoral growth and intending transformation of the informal sector in Africa. Twenty-nine studies dealing with this range of topics are examined in the framework of a systematic review. Although the reviews showed that the level of awareness on the benefits of adopting 4IR technologies in manufacturing SMEs is increasing, research has not highlighted the specific roles expected of SMEs in the digital revolution, especially in low-income countries like Africa. The study identified from the literature that if SMEs are fully transited into industry 4.0, small businesses in Africa will mobilise future jobs, create a new business model, and promote the internationalization of SME products, among others. The study proposed a framework to facilitate the role of SMEs in the 4IR. A unique regional approach towards governance and cooperation focusing on 4IR to grow the activities of the SMEs for regional development may be necessary for Africa. Received: 27 June 2021 / Accepted: 26 September 2021 / Published: 5 November 2021